Computation of the Reachability Graph of untimed Hybrid Petri nets - Fraca, Estibaliz; Júlvez, Jorge; Silva, Manuel (Jornada de Jóvenes Investigadores del I3A, 2014)
Untimed hybrid Petri nets are a formalism for the analysis of dynamical systems, which combines discrete and continuous behaviour. The study of its reachability is interesting for analysis purposes, such as the study of behavioural properties. A method to compute its reachability graph and reachability space is proposed here.